Standardisierte Inhaltsanalyse in Der Kommunikationswissenschaft – Standardized Content Analysis in Communication Research 2022
DOI: 10.1007/978-3-658-36179-2_21
|View full text |Cite
|
Sign up to set email alerts
|

Content Analysis in the Research Field of Technology Coverage

Abstract: Many technologies are fast-growing drivers of innovation and as such have the potential for major transformations of people’s lives. Related to that, technologies and particularly the development of new technologies (also called emerging technologies) call for a variety of actors who try to make themselves heard in the public sphere. Scientists, economic actors, politicians, regulators, and ordinary citizens try to have a voice in the public discussion about the development, implementation, and specific applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The predominant evaluation of quantum technology in TEDx talks is thus a positive one. This is similar to nanotechnology (a field closely related to quantum technology) as news media coverage mainly framed nanotechnology in terms of benefits (Gurr and Metag 2023). Due to the fact that risks are hardly mentioned in TEDx talks, we conclude that a narrow public good frame is present in that sense.…”
Section: Narrow Vs Wider Public Good Frame: Over Six Times More Benef...mentioning
confidence: 65%
See 1 more Smart Citation
“…The predominant evaluation of quantum technology in TEDx talks is thus a positive one. This is similar to nanotechnology (a field closely related to quantum technology) as news media coverage mainly framed nanotechnology in terms of benefits (Gurr and Metag 2023). Due to the fact that risks are hardly mentioned in TEDx talks, we conclude that a narrow public good frame is present in that sense.…”
Section: Narrow Vs Wider Public Good Frame: Over Six Times More Benef...mentioning
confidence: 65%
“…Cobb 2005, Druckman and Bolsen 2011, Achterberg 2014. Gurr and Metag (2023) found that the use of the benefit and risk frame vary depending on the technology, time period and media being analysed. For example, the frames most prominent in news media about nanotechnology are medical, scientific and economic benefits; carbon capture and storage is frequently framed in terms of political/legal and economic risks and benefits; and for synthetic biology, energy benefits are often mentioned (Gurr and Metag 2023).…”
Section: Narrow Vs Wider Public Good Frame Benefit Vs Risk Framementioning
confidence: 99%